As contribuições do projeto político-pedagógico das escolas do campo na sucessão da agricultura familiar e do desenvolvimento rural sustentável - Simonetti , Kerli Tatiane Grisa (2022)
The Political-Pedagogical Project - PPP - is one of the most relevant documents regarding the school environment, since it advises how a school can be organized, its goals set and the main objectives of an institution. Thus, it is required that it should be associated to the school context, which means Rural Education in this research. So, this trial aimed at understanding how the Rural Municipal Schools in Capitão Leônidas Marques city work and approach themes such as “familiar succession” and “sustainable rural development” to comprehend the relevance of familiar agriculture and sustainable development succession in the Political-Pedagogical Project. It was considered that there are weaknesses in the approaches to encouraging familiar succession and rural development, and that, despite the themes have been worked on, there is still a gap for further discussions and reflections among school, parents and students concerning the need and importance of these themes. It is a bibliographic and field research, supported by Bardin's Content Analysis. Finally, it should be highlighted that there are possibilities to foment familiar succession and their permanence in rural fields, based on incentives and policies that must improve rural conditions.